Research progress of extracellular vesicles as biomarkers in immunotherapy for non-small cell lung cancer - Ge, Yang; Ye, Ting; Fu, Siyun; Jiang, Xiaoying; Song, Hang; Liu, Bin; Wang, Guoquan; Wang, Jinghui (Frontiers in Immunology, 2023)
Lung cancer is one of the most severe forms of malignancy and the leading cause of cancer death worldwide, of which non-small-cell lung cancer (NSCLC) is the most primary type in the clinic. NSCLC is treated mainly with surgery, radiotherapy and chemotherapy, and targeted therapy and immunotherapy also have shown promising results in it. Including immune checkpoint inhibitors, several immunotherapies have been developed in clinical and benefited the NSCLC patients. However, immunotherapy faces the dilemma of poor response and unknown effective population. There is a critical need to identify novel predictive markers to further advance precision immunotherapy in NSCLC. Extracellular vesicles (EV) is an important research direction. In this review, we will focus on the biomarker role of EV in NSCLC immunotherapy from various perspectives, including the definition and properties of EV, biomarker role of EV in currently NSCLC immunotherapy, and different components of EV as biomarker in NSCLC immunotherapy research. We also crosstalked between biomarkers role of EV and novel technical approach or research concept in NSCLC immunotherapy, such as neoadjuvant, multi-omics analysis and tumor microenvironment. We hope this review would provide a reference for other research to improve the benefit for NSCLC patients from immunotherapy.